Pengaruh Rasio Keuangan terhadap Harga Saham pada Perusahaan Consumer Goods (Food and Baverage) yang Dimediasi GCG di Bei Periode 2019-2023 - Dwita Ashila Ramadhanty; Hariyati Hariyati (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This research aims to analyze the effects of profitability, liquidity, leverage, and valuation ratios on the stock prices of consumer goods and beverage companies listed on the Indonesia Stock Exchange during the period of 2019-2023. The method employed in this study is Structural Equation Modeling (SEM), with stock prices as the dependent variable and financial ratios as independent variables. Additionally, Good Corporate Governance (GCG), measured through the institutional ownership indicator, serves as a mediating variable. The sample consists of companies that meet specific criteria, utilizing annual financial statements and stock price data. The results indicate that the profitability ratio, measured by Return on Equity (ROE), has a positive and significant impact on stock prices. Liquidity ratios such as the Current Ratio (CR) also contribute to stock price determination, while leverage ratios Debt to Equity Ratio (DER) exhibit a negative influence. Valuation ratios measured by Price to Earnings Ratio (PER) play a crucial role in providing market insights into the intrinsic value of stocks. These findings suggest that investors should consider these financial ratios and GCG practices when making investment decisions in this sector.